2010 IEEE MTT-S International Microwave Symposium 2010
DOI: 10.1109/mwsym.2010.5517099
|View full text |Cite
|
Sign up to set email alerts
|

Channel temperature estimation in GaAs FET devices

Abstract: Operating channel temperature has an important influence on the electrical performance and reliability of GaAs FET amplifiers but this parameter is difficult to determine experimentally or analytically. Simplified closed-form and numerical models are commonly used although both are subject to errors in the case of sub-micron heat sources surrounded by epitaxial layers. Some assumptions about the heat source size and location are explored using finite-difference simulation. A simple measurement technique making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Channel temperature estimated with IR thermocamera, as already shown by other authors [3,5], showed a lower R TH value.…”
Section: Discussion About Experimental Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Channel temperature estimated with IR thermocamera, as already shown by other authors [3,5], showed a lower R TH value.…”
Section: Discussion About Experimental Resultssupporting
confidence: 69%
“…Over the last years, several techniques to evaluate junction temperature have been proposed in the literature [1][2][3][4][5][6][7][8]. Channel temperature and thermal resistance (R TH ) can be evaluated by means of electrical measurements, through the analysis of the variation of a temperature sensitive parameter (TSP) as a function of temperature and of the operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports on an electrical method (G-RTD) using gate resistance temperature dependence to determine device temperature in a straightforward manner [1][2][3]. A comparison of this method with micro-Raman spectroscopy has proved this method to be reliable with a net uncertainty of ±5% [4].…”
Section: Introductionmentioning
confidence: 99%